All rise : somebodies, nobodies, and the politics of dignity - Fuller, Robert W. (Robert Works), 1936- (BK currents book., 2006)
Robert Fuller's bestseller "Somebodies and Nobodies diagnosed and named the malady of rankism -- "what somebodies may do to nobodies." In this sequel, he further explores the social and psychological costs of this problem and counters it with the vision of a "dignitarian" society. Drawing on his experiences as a scientist, college president, and public diplomat, Fuller identifies rankism as the chief obstacle to achieving the American vision of liberty and justice for all -- and he spells out the steps required to eradicate it